THE IMPACT OF FINANCIAL INNOVATION ON FINANCIAL SUSTAINABILITY (AN ANALYTICAL STUDY OF THE IRAQI COMMERCIAL BANKING SECTOR FOR THE PERIOD (2019-2023)) - Ghassan Rashad Abdulhameed; Hayder Jasim Obaid; Haidar Hamoudi Ali Al Zubaidi (International Journal of Business, Law and Political Science, 2026)
Objective: This study aims to identify the relationship between financial innovations and financial sustainability. It also seeks to measure the level of financial innovations and the degree of financial sustainability. Method: Financial innovations were measured through six indicators: online banking transactions, banking transactions through banking agencies, ATM banking transactions, mobile banking transactions, ease of use of electronic banking services, and accessibility of electronic banking services. Financial sustainability was measured using a set of indicators: profitability, debt to equity ratio, current ratio, net profit to equity, and equity to assets ratio. The study focused on the Iraqi commercial banking sector, collecting data from the Iraq Stock Exchange and the Central Bank of Iraq for the period (2019-2023). Statistical programs such as SPSS and Excel were employed, and ANOVA analysis was used to explore the relationship between financial innovations and financial sustainability. Results: The results revealed an increasing trend towards the adoption of financial innovations and technology in banking operations across all measurement indicators. However, the study found that financial sustainability criteria were not met, except for the current ratio indicator, which did meet the sustainability standard. The study concluded that there is an influential relationship between financial innovations and financial sustainability. Novelty: Based on these findings, it is recommended that commercial bank managements increase their focus on financial innovations and promote a culture of technological transactions, as well as strengthen financial sustainability indicators as a strategic goal.